Evaluation of Women’s Performance in Grassroots Democracy: A Comparative Study of Upper Caste and Lower Caste Communities in Tamil Nadu - Dr. A. Puvi Lakshmi (Evaluation of Women’s Performance in Grassroots Democracy: A Comparative Study of Upper Caste and Lower Caste Communities in Tamil Nadu, Edition 1, 2024)
The landmark constitutional amendments of April 24, 1993, known as the 73rd and 74th amendments, were instrumental in promoting development in both rural and urban India. The 73rd and 74th Amendments aim to empower local governing bodies and provide women with autonomy to address issues within their jurisdiction, including service delivery at the local level, along with ensuring accountability. Elected women representatives, both as members and as sarpanchs, face numerous institutional and social hurdles. Institutional challenges include their ability to implement reforms, establish accountability mechanisms, decentralize functions and ensure active engagement. Despite inclusive provisions for marginalized communities, questions arise regarding the active participation of Dalits and women. Caste dynamics exacerbate the marginalization of women, especially lower caste women, and restrict their access to public forums due to intersecting gender and caste biases. To understand the various challenges faced by Dalit and non-Dalit women representatives in the Panchayat Raj system. Thus, the present research focuses on the comparative analysis of the performance of these two groups (Dalit and non-Dalit) of elected women representatives in the Panchayat Raj system. Assessing the performance of elected women representatives in panchayat activities holds importance for initiating essential changes in the Panchayati Raj Act. Moreover, such assessment proves beneficial for policymakers and planners in devising effective strategies at each stage of the Panchayati Raj Institutions (PRI).